Node.js in motion (Manning, 2018)
"Node in Motion is a fast-paced, practical video course designed to get you up to speed quickly on every aspect of Node. Following the expert and friendly guidance of PJ Evans, you'll master the key concepts like non-blocking JavaScript, asynchronous functions, using packages from the Node Package Manager (NPM), talking to the Internet, writing Web applications, interfacing with databases, and deploying your application. Everything you need to be a successful Node developer is covered in this great video course."--Resource description page